Posterior Cortical Atrophy: Does Complaint Match the Impairment? A Neuropsychological and FDG-PET Study - Guerrier, Laura; Cransac, Camille; Pages, Bérengère; Saint-Aubert, Laure; Payoux, Pierre; Péran, Patrice; Pariente, Jérémie (Frontiers in Neurology, 2019)
Objective: Posterior Cortical Atrophy (PCA) is a neurodegenerative disease characterised predominantly by visual impairment. However, diagnosis of PCA remains complicated with an interval of several years between initial reporting of symptoms and diagnosis. The aim of the present study is to define if patients’ visual and gestural complaints are consistent with their clinical profile. Method: an evaluation of daily visual problems as well as a full neuropsychological assessment and FDG-PET were performed in 15 PCA patients. We compared glucose metabolism between these PCA patients and 18 heathy controls. Correlation analyses were conducted in PCA patients between visual and gestural complaint, clinical impairments and brain glucose metabolism. Results: major impairment of cognitive functions was detected in PCA patients specifically in visual domains. Positive correlations were found between visual impairments and hypometabolism in the right temporo-parieto-occipital cortices. However, no correlation was found between complaint and visual impairment in PCA patients. Discussion: our main results suggest a consistent relationship between clinical impairment and brain metabolism. However, the patient’s complaint and visual performance are not linked. Combining the literature and our results, it seems that patients are generally aware of difficulties but misinterpret them. This misinterpretation may be responsible for the delayed diagnosis.